The Influence of Customer Engagement and Relationship Marketing Orientation on Customer Loyalty in GoFood Services: The Mediating Role of Trust - Pangestika, Adinda; Abror, Abror (Journal of Management and Administration Provision, 2025)
This study aims to examine and analyze the effects of customer engagement and relationship marketing orientation on customer loyalty in GoFood services, particularly within the local context of Padang, Indonesia, with trust as a mediating variable. This quantitative research collected data from 225 GoFood users in Padang using a structured questionnaire. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) software. Both customer engagement and relationship marketing orientation were modeled as second-order constructs using the repeated indicators approach. The results indicate that customer engagement does not significantly influence trust and customer loyalty, although both relationships are weakly positive. In contrast, relationship marketing orientation significantly and positively affects both trust and customer loyalty. Trust itself has a significant positive impact on customer loyalty. Mediation analysis revealed that trust does not mediate the relationship between customer engagement and customer loyalty, but successfully mediates the relationship between relationship marketing orientation and customer loyalty. These findings suggest that in the context of GoFood services in Padang, relationship-focused marketing strategies are more effective in fostering customer trust and loyalty than engagement effort alone. Strengthening trust remains essential for sustaining long-term loyalty in digital food delivery platforms.